Assessing benthic ecological status under impoverished faunal situations: A case study from the southern Gulf of Mexico. (August 2018) - Santibañez-Aguascalientes, Norma A.; Borja, Ángel; Kuk-Dzul, J. Gabriel; Montero-Muñoz, Jorge L.; Ardisson, Pedro-Luis
Abstract: Biological indices such as AZTI's Marine Biotic Index (AMBI) and multivariate AMBI (M-AMBI) have been used in monitoring programs worldwide to assess the benthic ecological status (ES) of transitional and coastal waters. However, their reliability is reduced under faunal impoverishment and defaunation, low abundance/number of taxa, and/or high percentage of taxa not assigned or mis-assigned to ecological group, which imply removing these data from the analysis. In order to avoid loss of robustness when these situations are met, here we propose an approach based on decision criteria that utilize these indices together with environmental and contaminants data. Our area of study is the southern Gulf of Mexico seafloor, where a survey was carried out during the rainy season across a sampling grid of 75 sites. To achieve this, we first distinguished homogeneous groups of sites and then defined states ('good', 'fair', and 'bad') from three sediment quality elements: benthic indices, environmental data by quartile values, and contaminant concentrations in the context of sediment quality guidelines. Overall, 69% of sampling sites showed low abundance and defaunation, mainly at sites located on the continental shelf, where most of them ranged from 'moderate' to 'poor' ES, principally by 'fair' environmental data and secondly, oil-related disturbance. Conversely, sites located near the mouths of rivers and coastal lagoons recorded the highest abundance and showed diverse sensitivity levels, ranging from 'high' to 'bad' ES. In conclusion, the use of this states-based approach allowed us to support and interpret the results of AMBI and M-AMBI, since their values were related to environmental and contaminants data. This approach may be useful in many contexts to avoid the loss of data when assessing the ES of the seafloor under defaunation or low abundance conditions.